A strong CD8+ T cell-stimulating supramolecular hydrogel. Issue 3 (8th January 2020) - Li, Xinxin; Wang, Youzhi; Wang, Siwan; Liang, Chunhui; Pu, Guojuan; Chen, Yaoxia; Wang, Ling; Xu, Huae; Shi, Yang; Yang, Zhimou
Abstract : The development of molecules with immune stimulatory properties is crucial for cancer immunotherapy. Abstract : The development of molecules with immune stimulatory properties is crucial for cancer immunotherapy. In this work, we combined two peptide-based molecules, tuftsin (TKPR) and Nap-G D F D F D Y, to develop a novel self-assembling molecule Nap-G D F D F D YTKPR (Comp. 3 ), which has strong CD8 + T cell stimulatory properties. Comp. 3 could self-assemble into nanofibers and hydrogels, which significantly improved the stability of tuftsin against enzyme digestion. The nanofibers of Comp. 3 enhanced the phagocytic activity of macrophages, promoted the maturation of DCs, and stimulated the expression of cytokines. In addition, it demonstrated an excellent anti-tumor efficacy in vivo by eliciting a strong CD8 + T immune response. Taken together, our observations revealed a powerful immune stimulating nanomaterial that is a promising compound for cancer immunotherapy.